NLRX1 Facilitates Histoplasma capsulatum-Induced LC3-Associated Phagocytosis for Cytokine Production in Macrophages - Huang, Juin-Hua; Liu, Chu-Yu; Wu, Sheng-Yang; Chen, Wen-Yu; Chang, Tzu-Hsuan; Kan, Hung-Wei; Hsieh, Sung-Tsang; Ting, Jenny P.-Y.; Wu-Hsieh, Betty A. (Frontiers in Immunology, 2018)
LC3-associated phagocytosis (LAP) is an emerging non-canonical autophagy process that bridges signaling from pattern-recognition receptors (PRRs) to autophagic machinery. LAP formation results in incorporation of lipidated LC3 into phagosomal membrane (termed LAPosome). Increasing evidence reveals that LAP functions as an innate defense mechanism against fungal pathogens. However, the molecular mechanism involved and the consequence of LAP in regulating anti-fungal immune response remain largely unexplored. Here we show that Histoplasma capsulatum is taken into LAPosome upon phagocytosis by macrophages. Interaction of H. capsulatum with Dectin-1 activates Syk and triggers subsequent NADPH oxidase-mediated reactive oxygen species (ROS) response that is involved in LAP induction. Inhibiting LAP induction by silencing LC3α/β or treatment with ROS inhibitor impairs the activation of MAPKs-AP-1 pathway, thereby reduces macrophage proinflammatory cytokine response to H. capsulatum. Additionally, we unravel the importance of NLRX1 in fungus-induced LAP. NLRX1 facilitates LAP by interacting with TUFM which associates with autophagic proteins ATG5-ATG12 for LAPosome formation. Macrophages from Nlrx1−/− mice or TUFM-silenced cells exhibit reduced LAP induction and LAP-mediated MAPKs-AP-1 activation for cytokine response to H. capsulatum. Furthermore, inhibiting ROS production in Nlrx1−/− macrophages almost completely abolishes H. capsulatum-induced LC3 conversion, indicating that both Dectin-1/Syk/ROS-dependent pathway and NLRX1-TUFM complex-dependent pathway collaboratively contribute to LAP induction. Our findings reveal new pathways underlying LAP induction by H. capsulatum for macrophage cytokine response.